2001
DOI: 10.2144/01305rr05
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Extrachromosomal Elements by Histone Immunoprecipitation

Abstract: Here, we describe a gentle and effective method for the rapid and reproducible isolation of histone-bound extrachromosomal DNA molecules called extrachromosomal elements (EEs). This method facilitates the harvest of a specific population of EEs following their isolation from cultured cells, primary tissues, and tumor cells. Active EEs are bound to histone proteins, and these histone-bound EEs carry actively transcribing genes such as c-myc. Our method exploits the presence of histones on EEs and serves as a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…The supernatant was phenol-chloroform extracted three times and the Hirt DNA was ethanol precipitated. To check for any genomic DNA contamination before phenol-chloroform extraction, the Hirt supernatant was subjected to methanol-acetic acid fixation on slides and examined by DAPI staining 48 . The precipitated Hirt DNA was also examined by standard electrophoresis agarose gel and ethidium bromide staining.…”
Section: Hirt Ecc Dna Isolation and Detectionmentioning
confidence: 99%
“…The supernatant was phenol-chloroform extracted three times and the Hirt DNA was ethanol precipitated. To check for any genomic DNA contamination before phenol-chloroform extraction, the Hirt supernatant was subjected to methanol-acetic acid fixation on slides and examined by DAPI staining 48 . The precipitated Hirt DNA was also examined by standard electrophoresis agarose gel and ethidium bromide staining.…”
Section: Hirt Ecc Dna Isolation and Detectionmentioning
confidence: 99%
“…Previously it has been shown that plasmids containing matrix attachment regions (MARs) are maintained in double minute extrachromosomal elements in HeLa cells [65]. These are autonomously replicating extrachromosomal elements that are up to a few Mb in size [66], have been known to be associated with active histones [67] and can be purified by histone immunoprecipitation [68]. MARs and scaffold attachment regions (SARs), together named as S/MARs, are regions on the DNA which attach to nuclear matrix and have been associated with functions such as anchoring of DNA, maintenance of nuclear architecture, regulation of transcription and replication.…”
Section: Discussionmentioning
confidence: 99%